Hubungan Pelaksanaan Tata Tertib Sekolah dengan Prestasi Belajar IPS Siswa Kelas V SD Gugus V - Mulyadi, Nur Annisa; Rosmalah, Rosmalah (Universitas Negeri Makassar, 2021)
The problem in this study is the lack of students' understanding of practice of discipline which makes students less disciplined and polite. This research is a quantitative study with a correlation design that aims to determine the relationship between the implementation of school rules and social studies learning achievement for Vth students of SD Gugus V. The data analysis technique with descriptive analysis obtained the implementation of school rules has an average of 85,65 and a percentage of 88,30% and the average social studies learning achievement of students has an average of 82,99 and a percentage of 87,35% with a very good category. Then based on the results of inferential statistical analysis, the tcount value (4,9654) is greater (>) the ttable value (1,67109) at the 5% significance level. Based on the analysis of the data above, it can be said that the implementation of the rules and learning achievement in the school was carried out well and there was a relationship between the two variables. From these conclusions, the impacts resulting from this study with the relationship between the implementation of school rules and learning achievement, it is known that the implementation of good school rules will improve student achievement.